Aspectos relacionados à internação hospitalar em adultos portadores de HIV/Aids - Silva, Cícera Eugênia Pereira da (2018)
Introduction: AIDS (Human Immunodeficiency Syndrome) is an important public health problem worldwide. In the country, after 30 years of the first AIDS case in 1981, the policy to confront the epidemic is recognized as an international reference. Objective: to analyze aspects related to hospitalization in adults with HIV / AIDS. Patients and Methods: This was a cross-sectional study, with description of variables and analysis of associations between HIV / AIDS patients. Carried out at the University Hospital of Aracaju / SE, in the infectious sector, between October 2016 and November 2017. The sample consisted of 40 HIV-reactive adults aged 18 years, literate or not. Data were described using simple and percentage frequencies. To evaluate the relationship between demographic, economic and behavioral characteristics related to the analysis of aspects of antiretroviral therapy and hospitalization, multiple correspondence analysis was applied to construct a perceptual map. Descriptive analysis was performed using frequencies and associations of variables, using Fisher's exact tests and 95% confidence intervals, using the R Core Team 2017 software. Results: Among the participants, 24 (60.0%) were men, 20 (50. 0%) were aged under 40 years and 27 (67.5%) with less than eight years of study, the predominant self-reported color was brown 25 (62.5%) with 22 (55.0%) of the participants residing in the great Aracaju. Regarding the epidemiological and behavioral aspects that led the patients to their hospitalization, 21 (52.5%) reported not having a fixed partnership, 24 (82,8%) reported transmission of HIV through the sexual, 35 (87.5%) reported heterosexual orientation and approximately one third of them reported not smoking, using illicit drugs or alcoholic beverages. Regarding hospital admission, 31 (77.5%) had a late diagnosis of HIV with AIDS-related illnesses, such as pneumonia 2 (5.0%) , tuberculosis 4 (10.0%) and Cerebral toxoplasmosis 4 (10%). Regarding the clinical reasons for hospitalization, 24 (60.0%) reported weakness, diarrhea and fever (15 / 40.5%), anemia 11 (27.5%). Conclusions: The data from this study allow us to affirm that men, young population and with little schooling are corroborating aspects for hospitalization. The predominance among the patients who presented a late diagnosis is worrisome, mainly because it reveals flaws in the health care processes.